2020
DOI: 10.1002/wsbm.1490
|View full text |Cite
|
Sign up to set email alerts
|

Regulating cellular cyclic adenosine monophosphate: “Sources,” “sinks,” and now, “tunable valves”

Abstract: A number of hormones and growth factors stimulate target cells via the second messenger pathways, which in turn regulate cellular phenotypes. Cyclic adenosine monophosphate (cAMP) is a ubiquitous second messenger that facilitates numerous signal transduction pathways; its production in cells is tightly balanced by ligand-stimulated receptors that activate adenylate cyclases (ACs), i.e., "source" and by phosphodiesterases (PDEs) that hydrolyze it, i.e., "sinks". Because it regulates various cellular functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…As we discussed early in this review, regulation of cAMP signaling is fine-tuned by various enzymes in the cells. Recently, Getz et al suggested that cAMP signaling is also regulated by GIV/Girdin (Guanine nucleotide-binding (G) protein α subunit (Gα)-interacting vesicle-associated protein), the prototypical member of a family of modulators of trimeric GTPases, Guanine nucleotide Exchange Modulators (GEMs) [ 143 ]. The same group of investigators demonstrated that GIV mRNA is almost undetectable in normal human livers, but GIV mRNA expression increases with an increasing degree of liver fibrosis [ 135 ].…”
Section: Camp Signaling In Aldmentioning
confidence: 99%
“…As we discussed early in this review, regulation of cAMP signaling is fine-tuned by various enzymes in the cells. Recently, Getz et al suggested that cAMP signaling is also regulated by GIV/Girdin (Guanine nucleotide-binding (G) protein α subunit (Gα)-interacting vesicle-associated protein), the prototypical member of a family of modulators of trimeric GTPases, Guanine nucleotide Exchange Modulators (GEMs) [ 143 ]. The same group of investigators demonstrated that GIV mRNA is almost undetectable in normal human livers, but GIV mRNA expression increases with an increasing degree of liver fibrosis [ 135 ].…”
Section: Camp Signaling In Aldmentioning
confidence: 99%
“…The loss of compartmentation in this context means that the system is no longer modifiable by the adrenoceptors. Counter-intuitively, the hydrolytic activity of PDEs can allow the persistence of high concentrations of cAMP within an effector microdomain through selective localization and source-to-sink fluxes [ 51 ]. The second and older notion of cAMP compartmentation is related to this, given that it was based on the idea of the ‘broadcast’ of cAMP.…”
Section: Camp Restriction and Compartmentationmentioning
confidence: 99%
“…As an activator of Gi and an inhibitor of Gs 14 using the same conserved GEM motif (Fig 7A ) GIV is known to tonically and robustly suppresses cAMP 15,50 , and by that token, it is expected to inhibit the cAMP surge. Because GIV-GEM was activated upon capacitation and remained active until the acrosome was shed (Fig 4F), we hypothesized that GIV's GEM function may be required for the prevention of a premature cAMP surge in the sperm head, and hence, premature acrosome exocytosis.…”
Section: Giv's Gem Function Suppresses Camp and Acrosomal Reactionmentioning
confidence: 99%